Analysis of MSME Management Strategies in Facing Competition in the Digital Era (A Case Study of D'SUM TO GO! Sukamandi) - Asep Sugito; Supriadi Supriadi; Inti Prihatin (JASS (Journal of Accounting for Sustainable Society), 2026)
The rapid changes in digital technology have altered the dynamics of business competition, including in the Micro, Small, and Medium Enterprises (MSMEs) sector. This condition encourages business actors to develop management strategies that are able to adapt to technological developments and changes in consumer behavior. This study aims to examine the management strategies implemented by the MSME D'SUM TO GO! Sukamandi in facing business competition in the digital era, while identifying factors that support and hinder its implementation. The study used a descriptive qualitative approach. Data were collected through field observations, in-depth interviews with business owners, and relevant documentation. The data were then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results show that D'SUM TO GO! Implements several strategies to maintain competitiveness, including utilizing social media as a promotional medium, improving product quality, improving service quality, and strengthening customer relationships. The use of digital technology contributes to expanding market access, improving communication with consumers, and strengthening the business's position amidst competition. However, several obstacles remain, such as limited human resources, suboptimal digital technology management capabilities, and high levels of competition in the culinary industry. This research confirms that implementing management strategies supported by digital technology plays a crucial role in maintaining business continuity and increasing the competitiveness of MSMEs. The research findings are expected to inform MSMEs' design of more adaptive, innovative business strategies that meet the demands of the evolving digital market. Keywords: Management Strategy, MSMEs, Competitiveness, Digitalization, Digital Marketing.